Early evolution of the angiosperm clade Asteraceae in the Cretaceous of Antarctica - Barreda, Viviana Dora; Palazzesi, Luis; Telleria, Maria Cristina; Olivero, Eduardo Bernardo; Raine, Ian; Forest, Félix (Proceedings of the National Academy of Sciences)
The Asteraceae (sunflowers and daisies) are the most diversefamily of flowering plants. Despite their prominent role in extantterrestrial ecosystems, the early evolutionary history of this familyremains poorly understood. Here we report the discovery of anumber of fossil pollen grains preserved in dinosaur-bearing depositsfrom the Late Cretaceous of Antarctica that drastically pushes backthe timing of assumed origin of the family. Reliably dated to ∼76?66Mya, these specimens are about 20 million years older than previouslyknown records for the Asteraceae. Using a phylogenetic approach,we interpreted these fossil specimens as members of anextinct early diverging clade of the family, associated with subfamilyBarnadesioideae. Based on a molecular phylogenetic tree calibratedusing fossils, including the ones reported here, we estimated that themost recent common ancestor of the family lived at least 80 Mya inGondwana, well before the thermal and biogeographical isolation ofAntarctica. Most of the early diverging lineages of the family originatedin a narrow time interval after the K/P boundary, 60?50 Mya,coinciding with a pronounced climatic warming during the Late Paleoceneand Early Eocene, and the scene of a dramatic rise in floweringplant diversity. Our age estimates reduce earlier discrepanciesbetween the age of the fossil record and previous molecular estimatesfor the origin of the family, bearing important implicationsin the evolution of flowering plants in general. Fil: Barreda, Viviana Dora. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales; Argentina Fil: Palazzesi, Luis. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales; Argentina. Royal Botanic Gardens; Reino Unido Fil: Telleria, Maria Cristina. Universidad Nacional de la Plata. Facultad de Ciencias Naturales y Museo; Argentina Fil: ...